Vocational Aspiration Of The Undergraduate Students- A Study (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Man responds to his environment by active degree of aspiration or aversion by movement towards or a way from flue exciting stimulus. In social life, aspiration is about one's education and occupation plays a major role in shaping one's destiny of life. Aspirations are the target a person sets for him to achieve which creates a 'desire' or 'will' in him. Formation of a strong desire and ambition motivates individual to strive hard to achieve that goal. Such motivation is keenly required if one has to succeed in life. If one goes through the education on a preferred vocation, he can get job satisfaction from the vocation and the individual shall be well placed. Aspiration adds to the efficiency of the person by exhibiting the best in him on the job. Therefore, before providing for education for a vocation, there is a need for planners to try to know which vocations are aspired by the students. Here in this study, different aspects of vocational aspiration was studied with 119 sample students by using simple random sampling technique with the help of self-constructed questionnaire as a tool.